2015
DOI: 10.1103/physrevlett.115.028001
|View full text |Cite
|
Sign up to set email alerts
|

Craters and Granular Jets Generated by Underground Cavity Collapse

Abstract: We study experimentally the cratering process due to the explosion and collapse of a pressurized air cavity inside a sand bed. The process starts when the cavity breaks and the liberated air then rises through the overlying granular layer and produces a violent eruption; it depressurizes the cavity and, as the gas is released, the sand sinks under gravity, generating a crater. We find that the crater dimensions are totally determined by the cavity volume; the pressure does not affect the morphology because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…Here we report that, if a silo filled with sand is vibrated or tapped before the discharge, the flow rate is not affected by the increase of packing fraction but the surface depression suffers an important change in geometry. The most remarkable effect is the observation of two external angles that contrast with the constant slope of conical depressions typically reported in the literature for standard packing conditions [11,28,32]. We found that these two angles appear because of the existence of two regions with distinct packing fractions: a peripheral stagnant zone and a less dense central zone flowing towards the aperture.…”
Section: Introductionsupporting
confidence: 56%
“…Here we report that, if a silo filled with sand is vibrated or tapped before the discharge, the flow rate is not affected by the increase of packing fraction but the surface depression suffers an important change in geometry. The most remarkable effect is the observation of two external angles that contrast with the constant slope of conical depressions typically reported in the literature for standard packing conditions [11,28,32]. We found that these two angles appear because of the existence of two regions with distinct packing fractions: a peripheral stagnant zone and a less dense central zone flowing towards the aperture.…”
Section: Introductionsupporting
confidence: 56%
“…The jet forms due to the collapse of the cavity created by the explosion. 22,[25][26][27][28][29] Without the confining walls, the jet is much stronger than that formed in 2D explosion. 21 The falling of the jet gives rise to an irregular hump at the center of the crater (Fig.…”
Section: Explosion Dynamicsmentioning
confidence: 99%
“…7 In general, with a selection of independent variables related to the material properties of explosives and granular media, a simple dimensional analysis shows that the size of explosion craters is bounded by the 1/3 and 1/4 scaling rules. 37 The analysis also shows that if the 1/3 scaling holds, the size of craters should be independent of the gravitational acceleration g. At low energy, explosion cratering near surface or in quasi-2D granular bed shows various different scaling rules, [20][21][22][23] as discussed in the introduction. It is important to examine how the scaling depends on the dimensionality and the burial depth of explosion events.…”
Section: Crater Size Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Badr et al (2016)) or the entrainment of the granular material from below (Varas et al 2009). Recently, the granular jets emitted by an underground cavity collapse have also been reported (Loranca-Ramos et al 2015).…”
Section: Introductionmentioning
confidence: 99%